2021
DOI: 10.1111/cge.13945
|View full text |Cite
|
Sign up to set email alerts
|

Mapping leprosy‐associated coding variants of interleukin genes by targeted sequencing

Abstract: Previous genotyping-based assays have identified non-coding variants of several interleukins (ILs) being associated with genetic susceptibility to leprosy. However, understanding of the involvement of coding variants within all IL family genes in leprosy was still limited. To obtain the full mutation spectrum of all ILs in leprosy, we performed a targeted deep sequencing of coding regions of 58 ILs genes in 798 leprosy patients (age 56.2 ± 14.4; female 31.5%) and 990 healthy controls (age 38.1 ± 14.0; female 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We conditioned the gene-wise association of IL18R1 for the p.G423R and observed that the additional amino acid changes remained nominally significantly depleted in the gene ( P SKAT-O = 0.02) indicating that an increasing burden of nonsynonymous variants in IL18R1 is protective for leprosy independent of the p.G423R mutation. Rare amino acid changes in IL18R1 had also been identified in a case-control study of Chinese leprosy patients [ 25 , 26 ]. When we combined IL18R1 rare variants (MAF < 1%) detected in the Chinese and the Vietnamese population samples, significant depletion was maintained for rare variants in leprosy cases ( P CAST = 0.001) surpassing multiple test correction ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conditioned the gene-wise association of IL18R1 for the p.G423R and observed that the additional amino acid changes remained nominally significantly depleted in the gene ( P SKAT-O = 0.02) indicating that an increasing burden of nonsynonymous variants in IL18R1 is protective for leprosy independent of the p.G423R mutation. Rare amino acid changes in IL18R1 had also been identified in a case-control study of Chinese leprosy patients [ 25 , 26 ]. When we combined IL18R1 rare variants (MAF < 1%) detected in the Chinese and the Vietnamese population samples, significant depletion was maintained for rare variants in leprosy cases ( P CAST = 0.001) surpassing multiple test correction ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Age was not included as a covariate as the control group had more time to be exposed and develop leprosy and therefore age would not be a confounder in our analysis. To test the combined effect of IL18R1 rare protein-altering variants identified by our study with those described for the Chinese population [ 25 , 26 ], we used a Cohort Allelic Sums Test (CAST) implemented in AssotesteR [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study in India showed that the locus on chromosome 10p13 is associated with an increased risk of PB-type leprosy. (35) The risk factor for leprosy from genetic factors can occur eight times with a range of 5.9-10.6 times. 36 Further research needs to be conducted to assess the correlation of serum TGF-β levels and IgM anti-PGL-1 levels not only in household contacts of multibacillary leprosy patients but to compare various types of leprosy in endemic areas and healthy people using the case-control method, and prognostic observations can be carried out with the cohort method with a larger sample.…”
Section: Auc: 775%mentioning
confidence: 99%
“…The role of IL-6 as an anti-inflammatory myokine is mediated through its inhibitory effect on Tumor Necrosis Factor (TNF)-alpha and IL-1, as well as the activation of IL-1 and IL-10. 3 Interleukin 6 can be used as a potential marker to identify the risk of household contacts becoming clinical leprosy. This risk is higher in low nutritional status (underweight, anemia, and iron deficiency).…”
Section: Introductionmentioning
confidence: 99%